Some Results on the Simultaneous Approximation (Analysis in Theory and Applications, 2014)
In this paper,  we give some results on the  simultaneous proximinal subset and simultaneous Chebyshev in the uniformly convex Banach space. Also we give relation between fixed point theory and simultaneous proximity.
Keywords: Simultaneous proximinal; simultaneous Chebyshev; fixed point.